2013
DOI: 10.1590/s1413-81232013001000027
|View full text |Cite
|
Sign up to set email alerts
|

Habilidades funcionais de crianças com deficiências em inclusão escolar: barreiras para uma inclusão efetiva

Abstract: Habilidades funcionais de crianças com deficiências em inclusão escolar -barreiras para uma inclusão efetivaFunctional skills of children with deficiencies in school inclusion -barriers to effective inclusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
3
0
4
Order By: Relevance
“…for possibilities of interventions more directed to areas of greater commitment. 13 As well as studies included in this investigation, other research states that physical activities have facilitated social inclusion. Moura et al (2012), points out that they favor the participation of people with various types of impairment, enabling their insertion in the sports environment and, consequently, their social inclusion.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…for possibilities of interventions more directed to areas of greater commitment. 13 As well as studies included in this investigation, other research states that physical activities have facilitated social inclusion. Moura et al (2012), points out that they favor the participation of people with various types of impairment, enabling their insertion in the sports environment and, consequently, their social inclusion.…”
Section: Resultsmentioning
confidence: 89%
“…Regarding the objective of the research, two studies used PEDI to assess school inclusion and the findings indicate that disability significantly compromises this process. In these studies, PEDI made it possible to identify individual disabilities contributing to the long-term monitoring of students, 13 besides, pointing out social function as the most compromised area, enabling the planning of interventions for children and their families in the research setting. 14 Analysis of the articles revealed that PEDI was used in research with children with Cerebral Palsy (CP) and occipital meningoencephalocele sequelae to analyze the benefits of aquatic physical activity 15,6 and equine therapy.…”
Section: Resultsmentioning
confidence: 99%
“…No que diz respeito à independência, aproximadamente, dois terços das crianças autistas comumente são incapazes de viver de forma independente e apenas um terço podem atingir algum grau de independência pessoal e de autossuficiência quando adultos 27 . Assim, é natural que, nesses relatos, os pais fiquem preocupados se os filhos serão independentes e se conseguirão relacionar-se com outras pessoas, especialmente no caso de sua ausência.…”
Section: Discussionunclassified
“…Amid the difficulties of children with disabilities to integrate into the school group, assessment tools are essential to provide information and insight for the school and families and, consequently, to promote inclusion 19 . They offer quantitative measures to assess the impact the disability could have on the child´s development, encouraging the establishment of goals and strategies for nursing care and intervention 20 , educational strategies, as well as protective and preventive measures for these children.…”
Section: Teachers´ Characteristicsmentioning
confidence: 99%